Computational and experimental analysis on Te-doped ZnSb thermoelectric material. (May 2018) - Pothin, R.; Ayral, R.M.; Berche, A.; Ziolkowski, P.; Oppitz, G.; Jund, P.
Graphical abstract: Highlights: Combined theoretical and experimental work on the Te-doping of thermoelectric ZnSb. DFT calculation predict the influence of oxygen impurity on doping. Experimental observation shows that Te-doped Zn4Sb3 is initially formed. Transient Potential-Seebeck Microprobe scanning (T-PSM) used as a doping sensor. An inert processing chain is a prerequisite for production of n-type ZnSb. Abstract: We report a combined theoretical and experimental work on the tellurium doping of thermoelectric ZnSb. We investigated the influence of tellurium on the phase's stabilities by DFT calculations. During experimental validation by SEM and EPMA characterization "needlelike" areas of Te-doped ZnSb were identified. The experimental results also highlight that for the compositions Zn0.5 Sb0.5-x Tex the system reaches a non-equilibrium state where ZnSb, ZnTe and Te-doped ZnSb are simultaneously present. The determination of the doping mechanism has demonstrated the formation of Te-doped Zn4 Sb3 after quenching, leading to the formation of Te-doped ZnSb due to the zinc diffusion during annealing. Presumed from experimental observation oxygen prevents the tellurium diffusion. These results lead to the conclusion of an inert processing chain as a prerequisite for production of n-type ZnSb, which puts hurdles on a cheap and easily scalable tellurium doping for homogeneous and competitive products.